Geophysical methods applied to the assessment of the geological and geotechnical conditions of dam sites: the case study of Pedrógão dam (Portugal) - Mota, R. (2015)
Geophysical methods are indirect tools of investigation of the subsoil. Seldom is the geophysicist able to confirm the results of his models with the reality. In the case study of Pedrógão dam, this was possible. At this site several geophysical methods were applied and compared with the geological and geotechnical map of the excavations for the dam’s foundation. This analysis allowed the conclusion of a good match between the main geophysical anomalies of each physical parameter with the identi fied main geological structures, namely an important fault zone – that could be a seepage source -, and also a good fit of the predicted in depth development of the geotechnical zones.